Intra‐operative protective mechanical ventilation in lung transplantation: a randomised, controlled trial. (11th July 2017) - Verbeek, G. L.; Myles, P. S.; Westall, G. P.; Lin, E.; Hastings, S. L.; Marasco, S. F.; Jaffar, J.; Meehan, A. C.
Summary: Primary graft dysfunction occurs in up to 25% of patients after lung transplantation. Contributing factors include ventilator‐induced lung injury, cardiopulmonary bypass, ischaemia‐reperfusion injury and excessive fluid administration. We evaluated the feasibility, safety and efficacy of an open‐lung protective ventilation strategy aimed at reducing ventilator‐induced lung injury. We enrolled adult patients scheduled to undergo bilateral sequential lung transplantation, and randomly assigned them to either a control group (volume‐controlled ventilation with 5 cmH2 O, positive end‐expiratory pressure, low tidal volumes (two‐lung ventilation 6 ml.kg −1, one‐lung ventilation 4 ml.kg −1 )) or an alveolar recruitment group (regular step‐wise positive end‐expiratory pressure‐based alveolar recruitment manoeuvres, pressure‐controlled ventilation set at 16 cmH2 O with 10 cmH2 O positive end‐expiratory pressure). Ventilation strategies were commenced from reperfusion of the first lung allograft and continued for the duration of surgery. Regular PaO2 /FI O2 ratios were calculated and venous blood samples collected for inflammatory marker evaluation during the procedure and for the first 24 h of intensive care stay. The primary end‐point was the PaO2 /FI O2 ratio at 24 h after first lung reperfusion. Thirty adult patients were studied. The primary outcome was not different between groups (mean (SD) PaO2 /FI O2 ratio control group 340 (111) vs. alveolar recruitment group 404 (153); adjusted p = 0.26). Patients in the control group had poorer mean (SD) PaO2 /FI O2 ratios at the end of the surgical procedure and a longer median (IQR [range]) time to tracheal extubation compared with the alveolar recruitment group (308 (144) vs. 402 (154) (p = 0.03) and 18 (10–27 [5–468]) h vs. 15 (11–36 [5–115]) h (p = 0.01), respectively). An open‐lung protective ventilation strategy during surgery for lung transplantation is feasible, safe and achieves favourable ventilation parameters.